Business economics I: microeconomics - Mukherjee, Debesh (New Central Book Agency, 2009)
Business economics I: microeconomics / Mukherjee, Debesh. -- Kolkata: New Central Book Agency, 2009 338.5 M954 No. of Copies : 1